(3cJGH aj GdTeS hGdbeQ dbQGWjS Hf EdjS GdHKfis - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s; (3bQGWjS Hf GdjGS GdHKfjs
(3ChdgG (B:s
(3GdMeO ddg fMeOg gPG cJGH bSWG d eUjQ Edi NGdO Hf jRjO Cfg Chd ef OYG dg HGdEeQI s
(3BNQgG (B:s
(3MJi CUGH GdWQjb GdeSJbje Edi gGgfG eG hLO efgPG GdeUfa hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B56 - (3U(B57s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B140 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(1641) s
Keywords: (3GdcjejGA h GdWHjYjGJs